2020
DOI: 10.3390/ani10091488
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Composition is Associated with Age and Memory Performance in Pet Dogs

Abstract: Gut microbiota can crucially influence behavior and neurodevelopment. Dogs show unique similarities to humans in their physiology and may naturally develop dementia-like cognitive decline. We assessed 29 pet dogs’ cognitive performance in a memory test and analyzed the bacterial 16S rRNA gene from fecal samples collected right after the behavioral tests. The major phyla identified in the dog microbiomes were Bacteroidetes, Firmicutes, and Fusobacteria, each represented by >20% of the total bacterial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
2
32
1
Order By: Relevance
“…On the other hand, the genus Ruminiclostridium 6 was positively correlated with NOIC performance and was significantly lower in abundance in CAF rats that received dietary intervention relative to chow-fed rats. Although little is known about the association between Ruminiclostridium 6 and memory performance, Actinobacteria has been associated with memory performance in dogs, albeit in an opposing direction compared with the present study as reduced abundance in that study was associated with better performance in a memory task [71]. Consistent with the present results, however, greater abundance of Proteobacteria has been correlated with memory dysfunction in adult mice whose mothers were fed a highfat diet before and during pregnancy [72].…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, the genus Ruminiclostridium 6 was positively correlated with NOIC performance and was significantly lower in abundance in CAF rats that received dietary intervention relative to chow-fed rats. Although little is known about the association between Ruminiclostridium 6 and memory performance, Actinobacteria has been associated with memory performance in dogs, albeit in an opposing direction compared with the present study as reduced abundance in that study was associated with better performance in a memory task [71]. Consistent with the present results, however, greater abundance of Proteobacteria has been correlated with memory dysfunction in adult mice whose mothers were fed a highfat diet before and during pregnancy [72].…”
Section: Discussionsupporting
confidence: 70%
“…Although the predominant phyla identified are similar to previous observations in healthy dogs, proportions vary among studies [ 57 , 58 , 59 ]. The canine breed, environmental conditions, age, weight, infections, sequencing technologies, and sequencing depth are responsible for significant variations reported for gut microbiota composition [ 18 , 19 , 20 , 21 , 22 , 23 ]. Here, there were more pronounced differences in the composition of fecal microbiota among 9-week-old puppies (D−8) compared to 21-week-old puppies (D85).…”
Section: Discussionmentioning
confidence: 99%
“…In adult dogs, the microbiota is stable over the years. Similar to humans, the composition of the canine gut microbiota is affected by several factors such as diet [ 16 ], body weight [ 18 ], geographic location [ 19 ], genetics [ 20 ], age [ 21 , 22 ], and infections [ 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of genera Alloprevotella and Paraprevotella was significantly lower in feces from dogs fed the OZ comparing to IZ, IZ +, and OZ +. Alloprevotella is one of the main genera identified in the dog microbiome ( Kubinyi et al, 2020 ), and studies, in dogs and other animal species, have shown that the dietary ratio of soluble and insoluble fiber can selectively regulate its intestinal abundance ( Chen et al, 2019 ; Sandri et al, 2019 ). However, as already stated, fiber content and type used in the present study did not differ between dietary treatments.…”
Section: Discussionmentioning
confidence: 99%